Isolation, Purification, Characterization of Tyrosinase from Button Mushroom - Sethi, Himani (My University, 2019)
A key enzyme Tyrosinase, responsible for melanin production in human, it is the black pigment of skin, eye and synthesis occurs in melanosomes present in melanocytes. Agaricus bisporus is the common edible mushroom from which tyrosinase has been extracted. Tyrosinase enzyme was purified by several techniques i.e. ammonium sulphate precipitation, dialysis followed by ion-exchange chromatography on DEAE cellulose. Fractions of protein obtained from ionexchange chromatography were concentrated and then applied to gel filtration chromatography to get pure protein. The purity and molecular mass of protein was confirmed by SDS-PAGE. The enzyme was purified and give 3.59% yield. An enzyme activity assay performed which confirmed that the enzyme tyrosinase is present. Then purified protein was characterized by Circular Dichroism, Fluorescence spectroscopy. Secondary structure of protein was characterized by CD in the UV- far region and it indicated that it is a β-sheet containing protein. To estimate the stability of protein against heat and denaturing agent was monitored by CD and Fluorescence spectroscopy. Denaturation curve analysis gave values of 2.88±0.12 kcal mol−1 and 4.11±0.09M for Δ°GD (Gibbs free energy change at 25°C) and Cm (midpoint of denaturation), respectively. GdmCl denaturation curve gives values which showed that the purified protein is stable.
Keywords: Agaricus Bisporous; Fluorescence; GdmCl; Cellulose; Tryptophan